X-radiation food intake study on rainbow trout (Oncorhyncus mykiss) fed diferent pellet sizes ration - Costa, Manuel da Silva (1997)
In aquaculture there is not enough scientific studies of feeding standards, and the improvement and implementation ot this knowledge could save labour and money for fish fanners and for the feed industry.